Impact of Educational Background on the Quality of Standardized Residency Training Program: The Case of China, a Cohort Study - Xiaoyu Tu; Xiaoquan Ding; Wanru Huang; Xiangrong Xu; Paulo Moreira; Runju Zhang (Health Services Insights)
Objectives: Residency training is important worldwide and recent studies have put more emphasis on its quality evaluation. This study aims to first explore the impact of educational backgrounds on the quality of gynecology and obstetrics (OB-GYN) standardized resident training (SRT) program in China, which may provide crucial evidence for policy considerations to improve SRT quality. Methods: A total of 397 OB-GYN resident graduates were enrolled in this retrospective cohort study. They were divided into three groups according to their educational background, that is Bachelor of Medicine (BM), Master of Medicine (MM), and Doctor of Medicine (DM) groups. The characteristics and the results of SRT graduation examination and annual assessment of these residents were collected and compared using one-way analysis of variance or Pearson’s chi-square test. A multivariable logistic regression analysis was performed to identify the association between sociodemographic variables and pass rates of SRT graduation examination. Besides, a subgroup analysis on training time for the DM group was performed. Strobe protocol was followed. Results: The residents were older in DM group than that in BM and MM groups ( P  < 0.001). There was significant difference of the training length and the proportion taking part in SRT graduation examination among three groups ( P  < 0.001). Although the written test scores of SRT graduation examination were the lowest in BM group ( P  = 0.015), there was no significant difference in other results among three groups. No significant variable was found associated with the pass rates of SRT examination. No significant difference was found in the subgroup analysis of DM group. Conclusion: Overall, the SRT quality of OB-GYN residents with different educational backgrounds was good and comparable. However, residents with BM degrees had lowest written scores and need to be strengthened during training. The training time of residents with DM degrees can be shortened according to their own conditions.